What Makes a Program Good? Evidence from Short-Cycle Higher Education Programs in Latin America and the Caribbean - Dinarte Diaz, Lelys; Ferreyra, Maria Marta; Urzua, Sergio; Bassi, Marina (World Bank, Washington, DC, 2021)
This paper explores the relationship between the practices, inputs, and other characteristics of short-cycle higher education programs (SCPs) and their students’ academic and labor market outcomes. A novel survey was designed and conducted to collect program-level information on quality determinants and program average outcomes for five countries in Latin America and the Caribbean. Quality determinants are grouped into the following categories: curriculum and training, infrastructure faculty, private sector engagement and job search assistance, costs and funding, and other practices related to student admission and institutional governance. In addition, individual-level data on SCP graduates was collected for Ecuador and matched to program survey data. Estimates from pooled survey data for the five countries indicate that specific quality determinants are positively associated with academic and labor market outcomes. Moreover, determinants account for about one-third of the explained variation in academic outcomes and formal employment. In contrast, estimates for Ecuador indicate that labor market outcomes are mostly associated with student and peer characteristics rather than program quality determinants. These findings can inform the design and replication of high-quality SCPs as well as their oversight and regulation.